The structural model of a sustainable coffee - based agrotechnology parks development in Bengkulu Province, Indonesia - Hamdan, H.,; Fauzi, A. M.,; Rusli, M. S.,; Rustiadi, E., (International Journal of Agricultural Technology, 2021)
Development of Science and Technology Parks (STP) is included in the Indonesia national development plans targeting 100 units during 2015-2019. Lack of understanding of the concept of technology parks causing the operation is not optimal. The influence of coffee-based agrotechnology parks (ATP) development factors in Kepahiang Regency was investigated. The obtained results by SEM pathways revealed variables with statistically significant effects, i.e., firstly, resource management strategies; secondly, social management strategies; thirdly, cooperation system strategies. These factors had a significant effect on ATP development. Resource management strategies and environmental management strategies had a significant effect on ATP development through cooperation system development. Identification of factors on the development of ATP and the relationship among factors are expected to help planners and decision-makers in strengthening development strategies of coffee agroindustry in the agrotechnology parks